Functional Soft Composites As Thermal Protecting Substrates for Wearable Electronics. (30th August 2019) - Shi, Yingli; Wang, Chengjun; Yin, Yafei; Li, Yuhang; Xing, Yufeng; Song, Jizhou
Abstract: Thermal management of wearable electronics integrated with biological tissues remains one of the critical challenges for their practical applications. The undesired heating can cause thermal discomfort or even thermal damage to biological tissues. Here, a novel thermal protecting substrate design is proposed for wearable electronics with abilities to manipulate the heat flow and efficiently absorb the excessive heat energy without the compromise of substrate flexibility. The thermal protecting substrate features a functional soft composite, which incorporates the embedded phase change material with a thin metal film on the top in a soft polymer. Compared with conventional substrate, the proposed thermal protecting substrate can reduce the peak temperature increase by over 85% with appropriate parameters. Experimental and numerical studies reveal the fundamental aspects of the design and operation of functional soft composite to effectively avoid excessive heating of biological tissues. Influences of geometrical parameters on temperature reduction are investigated. Device demonstration of thermal protecting substrate in a wearable heater on pig skin illustrates the unusual capability to reduce the maximum skin temperature, thereby enabling practical applications of wearable electronics and creating engineering opportunities in biointegrated applications requiring thermal protection of biological tissues. Abstract : A novel thermal protecting substrate design for wearable electronics with the ability to manipulate heat flow and efficiently absorb excessive heat energy without the compromise of substrate flexibility is reported. Compared with conventional substrate, the proposed thermal protecting substrate can reduce the peak temperature increase by over 85% with appropriate parameters.